Exploiting Indian landraces to develop biofortified grain sorghum with high protein and minerals - Nagesh Kumar, Mallela Venkata; Ramya, Vittal; Maheshwaramma, Setaboyine; Ganapathy, Kuyyamudi Nanaiah; Govindaraj, Mahalingam; Kavitha, Kosnam; Vanisree, Kalisetti (Frontiers in Nutrition, 2023)
Sorghum (Sorghum bicolor L. Moench) is the staple cereal and is the primary source of protein for millions of people in Asia and sub-Saharan Africa. Sorghum grain value has been increasing in tropical countries including India owing to its gluten-free nature, anti-oxidant properties and low glycemic index. However, the nutrient composition of modern cultivars is declining thus necessitating genetic biofortification of sorghum to combat malnutrition and improve nutritional balance in the human diet. Keeping this in view, efforts were made to utilize valuable alleles, associated with nutrient composition, that might have been left behind in the varietal development in sorghum. The study aimed to determine the genetic improvement for nine nutritional and quality parameters (crude protein, in vitro protein digestibility (IVPD), total iron (Fe), total zinc (Zn), bioavailable Fe (%), bioavailable Zn (%), total phenolics, tannins and antioxidant activity) in the grains of 19 sorghum genotypes (high yield, drought and grain mold tolerant) developed from 11 superior India's landraces. After selection and advancement made from 2017-2022 through single seed descent method, the improvement in the nine nutritional and quality parameters was assessed. Significant variation was observed for all the nine parameters among the landraces and the genotypes. Sorghum genotypes PYPS 2 and PYPS 13 recorded the highest crude protein (13.21 and 12.80 % respectively) and IVPD (18.68 and 19.56 % respectively). Majority of the sorghum genotypes recorded high Fe (14.21 -28.41 mg/100g) and Zn (4.81 -8.16 mg/100g). High phenolics and antioxidant activity were recorded in sorghum genotypes PYPS 18 (85.65 mg/g gallic acid equivalents) and PYPS 19 (89.78 %) respectively. Selections through SSD method revealed highest improvement in genotype PYPS 10 for crude protein (32.25 %), total phenolics (18.48 %) and antioxidant activity (15.43 %). High improvements in genotypes PYPS 12 (23.50%), PYPS 3 (26.79%), PYPS 15 (21.18 %) were recorded for total Fe, available Fe and high tannins respectively.The study demonstrated that landraces could be effectively utilized as a potential, low-cost and ecofriendly approach in sorghum genetic biofortification to improved sorghum productivity and nutritional supply in semi-arid tropics.